A Descriptive-Correlational Analysis of Financial Controls and Practices: A Case of Iglesia Filipina Independiente in The Diocese of Laoag - Glydel D. Arcena; Kyla Mae E. Barit; Jannmhelou M. Lalata; Tito Simon Jr. Q. Quitevis; Angelika D. Repotola (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
Religious organizations, practical churches, are considered to be one of the oldest organizations with a significant role in society. However, research on financial controls and practices of churches has been generally underexplored, and local studies are limited because church financial aspects are controversial in the country. This understanding calls for research that would describe the controls and practices of a religion called Iglesia Filipina Independiente. The outcome of such research would provide information to help assess their existing controls and practices and to help make informed decisions regarding improvement and changes. Therefore, this study described the financial controls and practices of the church. Thirty-two members of the finance committee among the churches in the Diocese of Laoag were the respondents. The survey was self-administered using a survey questionnaire, and the study used a descriptive correlational design. The collected data were analyzed using Pearson correlation analysis. The results showed that there is a very high level of implementation of financial controls and financial practices of the Church since the direction of the relationship is positively correlated. However, the findings suggested that there is also a need to improve financial controls under some components of financial statements, receipts, and disbursement that are often observed.This study was conducted not to question the faith but to contribute to the existing body of knowledge and serve as a reference for future researchers.